INVESTIGATION ON MECHANICAL BEHAVIOUR OF SELF COMPACTING CONCRETE REINFORCED WITH STEEL FIBRES (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Fibre reinforced self compacting concrete (SFRSCC) mingles the advantage of both Self compacting and fibre reinforced concrete. In the at hand investigation, the behavior and capability of SFRSCC in flexure and punching shear were tested by conducting experiments on prism and slab - column specimen to characterize the concrete reinforced with steel fibre volume fraction of 0.5 & 0.75%. Out of six concrete mixes considered for the study, three mixes were added with fibres and three without fibres. Flexural studies on prism resulted that incorporation of higher amount of steel fibres yielded higher toughness which enables the material to resist large deflections. Study on punching shear capacity reported that addition of fibres produced a substantial increase in capacity and is found to increase with addition of fibre dosage. Results indicated that at a constant volume fraction of fibres, improved performance in flexure and punching shear is observed in concrete mixes.